The effect of firm size, media exposure and industry sensitivity to corporate social responsibility disclosure and its impact on investor reaction - Andreas; Desmiyawatia; Liani, Warda (2015)
The purpose of this study is to examine the effect of firm size, media exposure and industry sensitivity to corporate social responsibility disclosure and its impact on investor reaction. This study population is a company listed on Indonesian Stock Exchange.Samples were taken by using purposive sampling method in order to obtain a sample of 53 companies.Data were analysed using partial least squares path modelling.The result reveals that firm size, media exposure and industry sensitivity have a significant effect on corporate social responsibility disclosure; firms size, media exposure and industry sensitivity does not directly effect on investor reaction; corporate social responsibility disclosure directly effect on investor reaction and mediates relationship between firm size, media exposure, industry sensitivity and investor reaction.